191k views
4 votes
What is the inverse of (x) =
√(x+9) x
\geq -9

f−1(x)=(x−9)2, x≥9
f to the power of negative 1 end exponent left parenthesis x right parenthesis equals left parenthesis x minus 9 right parenthesis squared, , , x is greater than or equal to 9

f−1(x)=−(x−9)2, x≤9
f to the power of negative 1 end exponent left parenthesis x right parenthesis equals negative left parenthesis x minus 9 right parenthesis squared, , , x is less than or equal to 9

f−1(x)=x2−9, x≥0
f to the power of negative 1 end exponent left parenthesis x right parenthesis equals x squared minus 9, , , x is greater than or equal to 0

f−1(x)=x2−9, x≤0

What is the inverse of (x) = √(x+9) x\geq -9 f−1(x)=(x−9)2, x≥9 f to the power of-example-1

1 Answer

2 votes

The inverse of
f, denoted
f^(-1), is such that


f\left(f^(-1)(x)\right) = x

Given
f(x)=√(x+9), we have


f\left(f^(-1)(x)\right) = \sqrt{f^(-1)(x) + 9} = x

Solve for
x.


\sqrt{f^(-1)(x) + 9} = x


\left(\sqrt{f^(-1)(x) + 9}\right)^2 = x^2


f^(-1)(x) + 9 = x^2


f^(-1)(x) = x^2 - 9

Note that
f(x)\ge0, so we must also have
f\left(f^(-1)(x)\right) = x \ge 0. This makes the third choice the correct one.

User Gaurang Shah
by
5.1k points